Evaluation of distribution transformer banks in electric power systems. (30th December 2011) - Olivares‐Galvan, Juan Carlos; Escarela‐Perez, Rafael; Georgilakis, Pavlos S.; Fofana, Issouf
SUMMARY This article compares the total mass and the total owning cost (TOC) of three‐phase distribution transformer banks with standard three‐phase distribution transformers. The comparison is based on the minimum TOC. This is achieved through a field‐validated distribution transformer design program that automatically minimises the objective function (TOC). In particular, 12 oil‐immersed distribution transformers are designed: 6 three‐phase transformer banks and 6 three‐phase transformers; these designs meet all the requirements of a given transformer standard. As a result, curves of minimum TOC versus transformer rating are obtained for three‐phase transformer banks and three‐phase transformers. Moreover, similar curves from seven transformer manufacturers are collected; the advantage of this collection is that these different manufacturers have different types of transformers: oil immersed or dry type, core or shell type, various voltage classes and power ratings, and so on, and consequently more general conclusions can be drawn regarding the comparison of three‐phase transformer banks and three‐phase transformers. From these investigations, it was found that from the viewpoint of minimum total mass and minimum TOC, three‐phase transformer banks should be recommended in case of small‐size transformers (rating lower than 45 kVA). This is an important finding that is not emphasised in recommended practices reported in transformer textbooks. Copyright © 2011 John Wiley & Sons, Ltd.